Comparison of radiation exposure between endoscopic ultrasound‐guided drainage and transpapillary drainage by endoscopic retrograde cholangiopancreatography for pancreatobiliary diseases. Issue 3 (19th August 2021) - Takenaka, Mamoru; Hosono, Makoto; Rehani, Madan M.; Chiba, Yasutaka; Ishikawa, Rei; Okamoto, Ayana; Yamazaki, Tomohiro; Nakai, Atsushi; Omoto, Shunsuke; Minaga, Kosuke; Kamata, Ken; Yamao, Kentaro; et al.
Abstract : Objectives: The transpapillary drainage by endoscopic retrograde cholangiopancreatography (ERCP‐D) cannot be performed without fluoroscopy, and there are many situations in which fluoroscopy is required even in endoscopic ultrasound‐guided drainage (EUS‐D). Previous studies have compared the efficacy, but not the radiation exposure of EUS‐D and ERCP‐D. While radiation exposure in ERCP‐D has been previously evaluated, there is a paucity of information regarding radiation doses in EUS‐D. This study aimed to assess radiation exposure in EUS‐D compared with that in ERCP‐D. Methods: This retrospective single‐center cohort study included consecutive patients who underwent EUS‐D and ERCP‐D between October 2017 and March 2019. The air kerma (AK, mGy), kerma‐area product (KAP, Gycm 2 ), fluoroscopy time (FT, min), and procedure time (PT, min) were assessed. The invasive probability weighting method was used to qualify the comparisons. Results: We enrolled 372 and 105 patients who underwent ERCP‐D and EUS‐D, respectively. The mean AK, KAP, and FT in the EUS‐D group were higher by 53%, 28%, and 27%, respectively, than those in the ERCP‐D group, whereas PT was shorter by approximately 11% (AK, 135.0 vs. 88.4; KAP, 28.1 vs. 21.9; FT, 20.4 vs. 16.0; PT, 38.7 vs. 43.5). The sub‐analysis limited to biliary drainage cases showed the same trend (AK, 128.3 vs. 90.9; KAP, 27.0 vs. 22.2; FT, 16.4 vs. 16.1; PT, 32.5 vs. 44.4). Conclusions: This is the first study to assess radiation exposure in EUS‐D compared with that in ERCP‐D. Radiation exposure was significantly higher in EUS‐D than in ERCP‐D, despite the shorter procedure time.